2017
DOI: 10.3390/molecules22010155
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fatigue Effects of the Unique Polysaccharide Marker of Dendrobium officinale on BALB/c Mice

Abstract: Dendrobium officinale extract shows potent anti-fatigue effects; however, the active substance responsible for these effects remains undetermined. A glucomannan with a huge molecular size of 730 kDa, called DOP, was identified as the unique authentication marker of this expensive herb. DOP exhibited immunomodulating effects on macrophages and lymphocytes in our previous study. Clinical reports also showed that people with fatigue syndrome have a disturbed immune system. Because DOP is the unique and dominant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…Numerous studies have shown that R. crenulata has neuroprotective, anti-tumor, anti-inflammatory, anti-depression, anti-fatigue, immune regulation, and other effects (Lekomtseva et al, 2017 ; Wei et al, 2017 ). Lin et al indicated that R. crenulata root extract (RCE), which contained 3.5% salidroside, regulated hepatic glycogen, and lipid metabolism in vitro (HepG2 cells) and in vivo (SD rats) via activation of the AMPK pathway (Lin et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that R. crenulata has neuroprotective, anti-tumor, anti-inflammatory, anti-depression, anti-fatigue, immune regulation, and other effects (Lekomtseva et al, 2017 ; Wei et al, 2017 ). Lin et al indicated that R. crenulata root extract (RCE), which contained 3.5% salidroside, regulated hepatic glycogen, and lipid metabolism in vitro (HepG2 cells) and in vivo (SD rats) via activation of the AMPK pathway (Lin et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The time when the mouse falls off was measured and scored as the following: 1, falling between 1 and 10 s; 2, between 11 and 25 s; 3, between 26 and 60 s; 4, between 60 and 90 s; 5, after 90 s. The forelimb grip strength test was performed in mice by using a grip strength meter (Columbus Instruments). The antifatigue experiment was performed as described [94]. Briefly, mice were placed in a swimming pool filled with fresh water at 25 ± 1˚C.…”
Section: Skeletal Muscle Function Analysismentioning
confidence: 99%
“…Nowadays, the development of natural products with the ability of reducing muscle injury and possessing anti-fatigue effects is becoming a major research focus ( 12 ). Previous studies have showed that Dendrobium officinale extract delays fatigue effects through enhancing glutathione peroxidase (GSH-Px) level and inhibiting malondialdehyde (MDA) content in serum ( 13 ). In the single exhaustive swimming test, dietary tea polyphenols can effectively protect against fatigue by inhibiting serum levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and IL-6, improving IL 10/TNF-α ratio in serum and reducing IL-1β mRNA expression in liver ( 14 ).…”
mentioning
confidence: 99%